From Storage to Survivorship: A Scoping Review of Young Adult Cancer Survivors’ Experiences and Preferences in Reproductive Survivorship Care After Fertility Tissue Preservation - Mottram, Rebecca; Feltbower, Richard G.; Jones, Georgina; Gelcich, Sarah; Rostron, Heather; Allen, Majorie; Glaser, Adam W. (Journal of pediatric & adolescent gynecology, 2025)
Despite improved survival rates for childhood cancer, around 60% of survivors suffer lifelong health problems due to their treatment, including fertility issues which account for one third of these problems. Ovarian or testicular tissue cryopreservation can be offered to patients whose cancer treatment puts them at high risk of subsequent subfertility, but it presents unique challenges compared to standard methods of fertility preservation. We report the available information on the experiences of cancer survivors who preserved tissue for future fertility, to support the development of survivorship care informed by recipients’ perspectives and experiences to identify future research priorities. We conducted a scoping review following the recommendations of the Joanna Briggs Institute and the Systematic Reviews and Meta-Analyses Extension for Scoping Review (PRISMA-ScR). From 1956 unique records, 5 met our inclusion criteria. No literature was found reporting on the experiences of people who stored testicular tissue. We found that young women who had stored ovarian tissue faced complex emotional and ethical dilemmas in reproductive decisions post cancer and strongly desired their own biological children. This scoping review is the first to report beyond clinical outcomes by focusing specifically on the self-reported outcomes of patients who preserved ovarian tissue in early life after a cancer diagnosis. Separate consideration of the needs of patients with stored fertility tissue is needed to enable personalized survivorship care. Patient-reported outcomes are also needed from individuals with stored testicular tissue, parents who consented to their child's tissue storage, and the healthcare professionals involved in their care.